Arbitrage pricing, transaction costs and taxation of capital gains - Litzenberger, Robert H.; Rolfo, Jacques (Journal of Financial Economics, 1984)
This paper examines one of the few cases of seemingly redundant securities: sets of three government bonds with the same maturity date. Within the bounds on relative bond prices established by tax-exempt investors in a market with proportional transaction costs, the taxation of capital gains on the basis of realization has a significant impact on relative prices. The empirical evidence supports the tax option effect discussed by Constantinides and Ingersoll, but does not generally support the segmented tax-clientele equilibrium discussed by Schaefer.